Tromboprofilaksa pri kirurških bolnikih s pljučno embolijo in globoko vensko trombozo v Splošni bolnišnici Murska Sobota - Kovačič, Alenka (Zdravniški vestnik, 2014)
Overview of thromboprophylaxis in surgical patients with pulmonary embolism and deep vein thrombosis in Murska Sobota General Hospital Background: Venous thromboembolism is the formation of clot in a deep vein, which causes completeor partial obstruction of the vein. This can be shown as a deep vein thrombosis or a pulmonary embolism. Deep vein thrombosis or pulmonary embolism, consequently, are a common complication after surgical procedures. Therefore, the need for appropriate guidelinebased preventive therapy of venous thromboembolism is crucial. The aim of our study was to determine the adequacy of preventive therapy for deep vein thrombosis or pulmonary embolism in surgical patients who were diagnosed with deep vein thrombosis or pulmonary embolism from 1.1.2007 to 31.12.2011 at the Murska Sobota General Hospital as a complication of surgical treatment and to compare the test group with the control group, in which there was no not either deep vein thrombosis or pulmonary embolism after surgical treatment. Methods: We reviewed the guidelines for the prevention of venous thromboembolism and determined the appropriate selection of drugs, the adequacy of dose and dosing interval, and the appropriate duration of therapy based on the risk assessment score provided by the guidelines. In the test group, we included 144 patients who were treated in the surgical department at the Murska Sobota General Hospital between 2007 and 2011 and had deep venous thrombosis or pulmonary embolism as main or associated diagnosis as a complication during surgical treatment. In the control group, we included 142 patients who were treated in the surgical department at the Murska Sobota General Hospital and did not had venous thromboembolism as the principal or accompanying diagnosis.Both groups were compared. Results: In the control group, 77% of patients received thromboprophylaxis according to the guidelines, while the proportion in the test group was 56%. Significant differences receiving adequate thromboprophylaxis (p <0.05) between the two groups were demonstrated with the chi-square test. Conclusion: According to the findings of our study we can conclude that the proportion of patients with adequate thrombo prophylaxis in surgical patients is still not optimal. The key to appropriate thromboprophylaxis is a good risks assessment of the patient and appropriate selection of thromboprophylaxis therapie. We believe, that it would be reasonable to introduce a formal and active strategies for the prevention of venous thromboembolism to provide the most appropriate protection of patients at increased risk.
Keywords: kirurški bolnik; nizkomolekularni heparin; Pljučna embolija; preprečevanje trombembolije; statistična obdelava podatkov; Venska tromboza